2014
DOI: 10.7554/elife.02736
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of fear memory by retrieval through reconsolidation

Abstract: Memory retrieval is considered to have roles in memory enhancement. Recently, memory reconsolidation was suggested to reinforce or integrate new information into reactivated memory. Here, we show that reactivated inhibitory avoidance (IA) memory is enhanced through reconsolidation under conditions in which memory extinction is not induced. This memory enhancement is mediated by neurons in the amygdala, hippocampus, and medial prefrontal cortex (mPFC) through the simultaneous activation of calcineurin-induced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 43 publications
9
86
0
Order By: Relevance
“…However, another study (Coccoz et al, 2011) using a similar stressor found that this stressor, when applied after memory reactivation, strengthened the memory. Similar findings have been obtained in a number of other studies (Fukushima et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…However, another study (Coccoz et al, 2011) using a similar stressor found that this stressor, when applied after memory reactivation, strengthened the memory. Similar findings have been obtained in a number of other studies (Fukushima et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, all three of these molecules seem to be specifically involved in extinction, but not in the initial acquisition of fear conditioning (Cain et al 2002;Marsicano et al 2002;Baumgärtel et al 2008;Havekes et al 2008). The three of them have also been reported to be required for memory destabilization during reconsolidation (Suzuki et al 2008;Kim et al 2011;De Oliveira Alvares et al 2013;Fukushima et al 2014), along with other mechanisms such as AMPA receptor endocytosis (Hong et al 2013) and protein degradation through the ubiquitin-proteasome system (Lee 2008;Lee et al 2008;Sol Fustiñana et al 2014). This is in line with the view that these molecular components could be part of a system involved in the labilization of synaptic plasticity established by consolidation of the original memory trace (Almeida-Corrêa and Amaral 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all three mechanisms seem to interact in endocannabinoid-mediated LTD in the hippocampus, with calcineurin apparently integrating the postsynaptic activation signal provided by LVGCCs and the presynaptic signal mediated by CB1 receptors (Heifets et al 2008). Calcineurin has also been shown to activate downstream targets that can mediate synaptic depression phenomena, such as AMPA receptor endocytosis (Beattie et al 2000;Kim et al 2007) and protein degradation through the ubiquitin-proteasome system (Fukushima et al 2014). Notably, both of these …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work from our laboratory has demonstrated that IA memory can undergo reconsolidation dependent on mTOR activity in the hippocampus and amygdala after retrieval (Jobim et al 2012). Reconsolidation might serve to maintain (Jobim et al 2012) or strengthen (Fukushima et al 2014;Pedroso et al 2013) IA memory.…”
Section: Discussionmentioning
confidence: 88%